+0  
 
-1
371
2
avatar+41 

My math program says that you can transform....

 \(1/sec\theta * tan\theta = sin\theta \)

Into...

\(tan^2\theta + 1 = sec^2\theta\)

Could someone explain how they made this transition? Thanks!

 Oct 20, 2017

Best Answer 

 #2
avatar+21191 
+2

My math program says that you can transform....
\(1/sec\theta * tan\theta = sin\theta\)
Into...
\(tan^2\theta + 1 = sec^2\theta\)
Could someone explain how they made this transition?

 

\(\begin{array}{|rcll|} \hline \frac{1}{\sec(\theta)} * \tan(\theta) &=& \sin(\theta) \quad & | \quad \cdot \sec(\theta) \\ \tan(\theta) &=& \sin(\theta) \cdot \sec(\theta) \quad & | \quad \text{square both sides} \\ \tan^2(\theta) &=& \sin^2(\theta) \cdot \sec^2(\theta) \quad & | \quad \sin^2(\theta) + \cos^2(\theta) = 1 \text{ or } \sin^2(\theta) = 1-\cos^2(\theta) \\ \tan^2(\theta) &=& [~1-\cos^2(\theta)~] \cdot \sec^2(\theta) \\ \tan^2(\theta) &=& \sec^2(\theta) - \cos^2(\theta) \cdot \sec^2(\theta) \quad & | \quad \sec^2(\theta) = \frac{1}{\cos^2(\theta)} \\ \tan^2(\theta) &=& \sec^2(\theta) - \cos^2(\theta) \cdot \frac{1}{\cos^2(\theta)} \\ \tan^2(\theta) &=& \sec^2(\theta) - \frac{\cos^2(\theta)}{\cos^2(\theta)} \quad & | \quad \frac{\cos^2(\theta)}{\cos^2(\theta)} = 1 \\ \tan^2(\theta) &=& \sec^2(\theta) - 1 \quad & | \quad +1 \\ \mathbf{\tan^2(\theta)+1} &\mathbf{=}& \mathbf{\sec^2(\theta)} \\ \hline \end{array}\)

 

laugh

 Oct 20, 2017
 #1
avatar+95859 
+1

Here's a ( highly questionable ) proceedure.......

 

1/sec * tan  =  sin

 

cos * sin/cos  = sin

 

sin  = sin                multiply both sides by the sin

 

sin^2  = sin^2

 

sin^2  =  1 - cos^2       add cos^2  to both sides

 

sin^2 + cos^2  =  1       divide through by cos^2

 

sin^2 / cos^2    + 1  =  1 / cos^1

 

tan^2  +  1  =  sec^2

 

Note :  multiplying/dividing on both sides of an identity isn't usually allowed......!!!!

 

 

cool cool cool

 Oct 20, 2017
edited by CPhill  Oct 20, 2017
edited by CPhill  Oct 20, 2017
 #2
avatar+21191 
+2
Best Answer

My math program says that you can transform....
\(1/sec\theta * tan\theta = sin\theta\)
Into...
\(tan^2\theta + 1 = sec^2\theta\)
Could someone explain how they made this transition?

 

\(\begin{array}{|rcll|} \hline \frac{1}{\sec(\theta)} * \tan(\theta) &=& \sin(\theta) \quad & | \quad \cdot \sec(\theta) \\ \tan(\theta) &=& \sin(\theta) \cdot \sec(\theta) \quad & | \quad \text{square both sides} \\ \tan^2(\theta) &=& \sin^2(\theta) \cdot \sec^2(\theta) \quad & | \quad \sin^2(\theta) + \cos^2(\theta) = 1 \text{ or } \sin^2(\theta) = 1-\cos^2(\theta) \\ \tan^2(\theta) &=& [~1-\cos^2(\theta)~] \cdot \sec^2(\theta) \\ \tan^2(\theta) &=& \sec^2(\theta) - \cos^2(\theta) \cdot \sec^2(\theta) \quad & | \quad \sec^2(\theta) = \frac{1}{\cos^2(\theta)} \\ \tan^2(\theta) &=& \sec^2(\theta) - \cos^2(\theta) \cdot \frac{1}{\cos^2(\theta)} \\ \tan^2(\theta) &=& \sec^2(\theta) - \frac{\cos^2(\theta)}{\cos^2(\theta)} \quad & | \quad \frac{\cos^2(\theta)}{\cos^2(\theta)} = 1 \\ \tan^2(\theta) &=& \sec^2(\theta) - 1 \quad & | \quad +1 \\ \mathbf{\tan^2(\theta)+1} &\mathbf{=}& \mathbf{\sec^2(\theta)} \\ \hline \end{array}\)

 

laugh

heureka Oct 20, 2017

13 Online Users

avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.